1999
DOI: 10.1091/mbc.10.7.2297
|View full text |Cite
|
Sign up to set email alerts
|

The Movement of Coiled Bodies Visualized in Living Plant Cells by the Green Fluorescent Protein

Abstract: Coiled bodies are nuclear organelles that contain components of at least three RNAprocessing pathways: pre-mRNA splicing, histone mRNA 3Ј-maturation, and pre-rRNA processing. Their function remains unknown. However, it has been speculated that coiled bodies may be sites of splicing factor assembly and/or recycling, play a role in histone mRNA 3Ј-processing, or act as nuclear transport or sorting structures. To study the dynamics of coiled bodies in living cells, we have stably expressed a U2BЉ-green fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
122
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 58 publications
12
122
1
Order By: Relevance
“…These findings indicate that the nucleolar subdomain where AGO4 colocalizes with RDR2, DCL3, NRPD1b, and various siRNAs are Cajal bodies, or related entities. The fact that these AGO4 bodies can be found inside the nucleolus, or on the outer edge of the nucleolus, is consistent with other observations of the dynamic nature of Cajal bodies (Boudonck et al 1999;Cioce and Lamond 2005). Previously described associations of Cajal bodies with chromatin, such as histone genes and telomeres, to deliver histone mRNA processing or telomerase RNPs, respectively, suggest that the trafficking of RISCs to heterochromatic loci via Cajal body intermediates is plausible.…”
Section: A Connection Between the Nuclearsupporting
confidence: 88%
“…These findings indicate that the nucleolar subdomain where AGO4 colocalizes with RDR2, DCL3, NRPD1b, and various siRNAs are Cajal bodies, or related entities. The fact that these AGO4 bodies can be found inside the nucleolus, or on the outer edge of the nucleolus, is consistent with other observations of the dynamic nature of Cajal bodies (Boudonck et al 1999;Cioce and Lamond 2005). Previously described associations of Cajal bodies with chromatin, such as histone genes and telomeres, to deliver histone mRNA processing or telomerase RNPs, respectively, suggest that the trafficking of RISCs to heterochromatic loci via Cajal body intermediates is plausible.…”
Section: A Connection Between the Nuclearsupporting
confidence: 88%
“…Differences in the HYL1 protein level affect miRNA metabolism and mRNA stability but not dsRNA-mediated PTGS. HYL1 is predominantly a nuclear protein and is detected in nuclear bodies and ring-like structures reminiscent of Cajal or coiled bodies, known to be involved in nuclear RNA processing in association with the nucleolus (45,46). One-third to one-half of the HYL1 protein in crude extracts is in the form of an Ϸ300-kDa complex.…”
Section: Dsrna-mediated Ptgs Is Not Compromised In the Hyl1 Mutantmentioning
confidence: 99%
“…Recent studies have shown that CB components reside for relatively short times in CBs, suggesting that molecular events occur in CBs in the context of a dynamic exchange of factors with the surrounding nucleoplasm (Handwerger et al, 2003;Dundr et al, 2004). In addition, CBs themselves are highly dynamic, in that they move, split, and fuse during the lifetime of the cell (Andrade et al, 1993;Boudonck et al, 1999;Platani et al, 2000); moreover, their structure is dependent on active transcription and metabolic activity, suggesting that a constant supply of substrates is required to maintain CB integrity (Carmo-Fonseca et al, 1992;Boudonck et al, 1998;Shpargel and Matera, 2005;Lemm et al, 2006). Although it is formally possible that the occurrence of CBs in nuclei is an indirect outcome of physiological state, speculation has focused in recent years on the possibility that concentration of components facilitates key steps in gene expression.…”
Section: Introductionmentioning
confidence: 99%